2022
DOI: 10.3390/ani12213034
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interactive Effects of Thymol and Thymoquinone: Moving towards an Enhanced Performance, Gross Margin, Immunity and Aeromonas sobria Resistance of Nile Tilapia (Oreochromis niloticus)

Abstract: Plant-derived bioactive compounds with promising nutritional and therapeutic attributes (phytogenics) are among the top priorities in the aquaculture sector. Therefore, the impact of thymol (Thy) and/or thymoquinone (ThQ) on the growth, immune response antioxidant capacity, and Aeromonas sobria (A. sobria) resistance of Nile tilapia was investigated. Four fish groups were fed a control diet and three basal diets supplemented with 200 mg/kg diet of Thy or ThQ and a blend of both Thy and ThQ at a level of 200 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 79 publications
(150 reference statements)
6
23
0
Order By: Relevance
“…In this regard, herein, dietary inclusion of LEOs significantly increased the expression levels of genes encoding gut barrier functions and TJP (MUC-2, JAM-2, and occludin) in broilers, suggesting its promising role in maintaining the gastrointestinal barrier functions. In agreement with our results, previous studies stated that encapsulated carvacrol and thymol mixture, oregano EO ( Liu et al, 2019 ), carvacrol and thymol mixture, and a mixture of carvacrol, trans-cinnamaldehyde and thymol EOs ( Aljazzar et al, 2022 ; Ibrahim et al, 2022b ) had provoked the expression level of occludin gene in broilers. Similarly, recent studies reported that the expression levels of MUC-2, JAM-2, and occludin genes were upregulated following dietary inclusion of eugenol nanoemulsion ( Ibrahim et al, 2022a ), thymol nanoemulsion ( Ibrahim et al, 2021a ), garlic nanohydrogel, and blend of EOs ( Aljazzar et al, 2022 ) in broilers.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this regard, herein, dietary inclusion of LEOs significantly increased the expression levels of genes encoding gut barrier functions and TJP (MUC-2, JAM-2, and occludin) in broilers, suggesting its promising role in maintaining the gastrointestinal barrier functions. In agreement with our results, previous studies stated that encapsulated carvacrol and thymol mixture, oregano EO ( Liu et al, 2019 ), carvacrol and thymol mixture, and a mixture of carvacrol, trans-cinnamaldehyde and thymol EOs ( Aljazzar et al, 2022 ; Ibrahim et al, 2022b ) had provoked the expression level of occludin gene in broilers. Similarly, recent studies reported that the expression levels of MUC-2, JAM-2, and occludin genes were upregulated following dietary inclusion of eugenol nanoemulsion ( Ibrahim et al, 2022a ), thymol nanoemulsion ( Ibrahim et al, 2021a ), garlic nanohydrogel, and blend of EOs ( Aljazzar et al, 2022 ) in broilers.…”
Section: Discussionsupporting
confidence: 93%
“…In line with the provoked nutrient digestibility and digestive enzymes` activities in LEOs-supplemented groups, the transcription levels of genes encoding digestive enzymes (AMY2A, CCK, and PNLIP) were also elevated. The synthesis of digestive enzymes can be altered by hormones, genes, and dietary feed supplements ( Ibrahim et al, 2022b ). Furthermore, the upregulation of genes encoding digestive enzymes reflected the significant role of specific nutritional aids or even their adaptations by animals ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in seabreams; furthermore, the fungal pathogens Saprolegnia spp. and the parasites Trichodina , Chilodonela , Argulus , and Ergasilus , as well as Leeches have been known for a long time ( Kim et al, 2017 ; Buján et al, 2018 ; Duman et al, 2021 ; Abd El-Hack et al, 2022 ; Shahin et al, 2022 ; Ibrahim et al, 2022a , b ). However, many unknown or emerging etiological diseases still appear frequently in aquatic farms, seriously affecting the development of aquaculture ( Shahin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%